Communication and access to healthcare: Experiences of Aboriginal and Torres Strait Islander people managing pain in Queensland, Australia - Bernardes, Christina Maresch; Houkamau, Kushla; Lin, Ivan; Taylor, Marayah; Birch, Stephen; Claus, Andrew; Bryant, Matthew; Meuter, Renata; Isua, Jermaine; Gray, Paul; Kluver, Joseph P; Jones, Corey; et al. (Frontiers in Pain Research, 2022)
Background: Pain management requires a multidisciplinary approach and a collaborative relationship between patient-provider in which communication is crucial. This study examines the communication experiences of Aboriginal and Torres Strait Islander patients and Aboriginal and Torres Strait Islander Hospital Liaison Officers (ATSIHLOs), to improve understanding of how pain is managed in and through patient-health professional communication. Methods: This qualitative study involved a purposive sample of patients attending three persistent pain clinics and ATSIHLOs working in two hospitals in Queensland, Australia. Focus groups and in-depth interviews explored the communication experiences of patients managing pain and ATSIHLOs supporting patients with pain. This study adopted a descriptive phenomenological methodology, as described by Colaizzi (1978). Relevant statements (patient and ATSIHLOs quotes) about the phenomenon were extracted from the transcripts to formulate meanings. The formulated meanings were subsequently sorted into thematic clusters and then integrated into themes. The themes were then incorporated into a concise description of the phenomenon of communication within pain management. Findings were validated by participants. Results: A total of 21 Aboriginal and Torres Strait Islander participants were involved in this study. Exploration of the communication experiences of patients and ATSIHLOs revealed overlapping themes of important barriers to and enablers of communication that affected access to care while managing pain. Acknowledging historical and cultural factors were particularly important to build trust between patients and health professionals. Some patients reported feeling stigmatized for identifying as Aboriginal and Torres Strait Islander, while others were reluctant to disclose their background for fear of not having the same opportunity for treatment. Differences in the expression of pain and the difficulty to use standard pain measurement scales were identified. Communication was described as more than the content delivered, is visual and emotional expressed through body language, voice intonation, language and the speed of the conversation. Conclusion: Communication can significantly affect access to pain management services. Aboriginal and Torres Strait Islander patients highlighted the burden of emotional pain caused by historical factors, negative stereotypes and the fear of discrimination. Pain management services and their health professionals need to acknowledge how these factors impact patients their trust and care.